Cabinets in Western Europe
XII, 300 p.
Keywords: A fully-updated second edition of the presentation of the structure and workings of the national cabinets in Western European countries today. This book is based on a common framework which enables the reader to compare the origins, structure, composition and activities of these cabinets and to draw lessons from this comparison. Emphasis is placed on the leadership and on the character of coalitions. When West European ministers are working ever more closely together, a knowledge of the life of national cabinets is vital as is an understanding of the differences between types of cabinet decision-making in the context of the reforms proposed of Western European governments.